STUDI ASPEK PERTUMBUHAN UDANG NENEK (Harpiosquilla raphidea) DI PERAIRAN JUATA LAUT KOTA TARAKAN - Chandra, Tommy; Abdul Latif, Adil; Kalalo, Alfretse; Salim, Gazali (Jurnal Harpodon Borneo, 2014)
Type shrimp fishermen in Tarakan in category Discard the shrimp Nenek (Harpiosquilla raphidea). Results of interviews with fishermen Juata Tarakan city, saying that this type of shrimp is a type of shrimp discard or catches that do not have a high economic value and if this shrimp caught by the fishermen of this type in the return to nature/ocean. This is different the opinion from Firdaus and Salim (2013) that the results of the study to test proteins from different species of shrimp nenek (Harpiosquilla raphidea) protein values obtained meat for shrimp nenek (Harpiosquilla raphidea) that is equal to 16.49%. The purpose of research is to investigate the growth of morphometry Harpiosquilla Raphidea (correlation relationship between body weight and carapace with correlation relationship between body length and body weight).Methods of research used descriptive method. Shrimp Nenek sampling using sampling in the waters juata based on catches of fishermen juata Tarakan city. Sampling was conducted using purposive sampling as much as 6 times with the consideration that the sampling 6 times expected to represent the population of shrimp Nenek in the waters Juata Tarakan City. Sampling was carried out during low tide situation. The main variables measured in this study is the morphology shrimp Nenek is carapace (carapace and long thick carapas), shrimp body length (total length and standard length) and the shrimp body weight (total weight and dry weight / meat). The variables measured were supporting habitat conditions / environment of shrimp Nenek in the waters Juata Tarakan city. Data analysis using regression equation is the relationship between the length (body length and carapace length) with body weight (total weight and meat weight) shrimp Nenek.The results showed an average of the data research on the relationship between total length with a total weight of shrimp Nenek allometri had negative growth and a very strong relationship. The results showed an average of research data on the relationship of carapace length with a weight meat of shrimp Nenek had allometri negative growth and a very strong relationship. Keywords : Shrimp nenek ; Harpiosquilla raphidea; morphometry; growth; discard